Strategi Bisnis dengan Strategi Sistem Informasi untuk Perguruan Tinggi - Hendy Wijaya; Suparto Darudiato; Tanty Octavia (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Information systems strategy is one important aspect in determining the direction and goals of an organization/ company. Well-directed strategic planning will bring positive influence on the existence of an organization in aligning with the vision planned in the early stages as well as in achieving the objectives. Ineducation, strategic planning of a higher education institution plays an important role to determine the objectives to be achieved. Nowadays, competition in education is no less intense with world trade, so it requires appropriate strategic planning of any relevant factors. In this research, data collection is done by a direct survey and questionnaires at several higher educational institutions, and supported with literature study. Based on the survey, a model is created as a solution for common problems faced by the institution. Decisions through better information systems strategy will make a positive contribution to the development and quality objectives of the institution that may increase its competitiveness.